Future Thinking and Its Relationship to the Level of Ambition among Students of the Institute of Fine Arts - Kajwan Nassif, Qasim Khalaf (Journal of Tikrit University for Humanities, 2024)
The aim of the research is to reveal the level of future thinking and the level of ambition among the students of the Institute of Fine Arts in Tikrit and to identify the significance of the differences in the concept of thinking about the future. Also, it is concerned with the level of ambition among the students of the Institute of Fine Arts in Tikrit according to the variable of specialization (plastic - design), and to verify the nature of the correlation between future thinking and the level of ambition among students of the Institute of Fine Arts in Tikrit. The research sample was (136) students who were selected by a comprehensive enumeration method from the students of the institute in Tikrit due to the smallness of the research community, at an average of (103) art students and (53) students from the design department. To achieve the research objectives, a scale was built to measure future thinking, and a quality scale was adopted (2014) to measure the level of ambition. To treat the research data statistically, the researcher used several statistical methods, including chi-square, percentage ratio, t-test for one sample, t-test for two independent samples, Pearson’s correlation coefficient, Gutman’s equation, and Spearman’s equation for correction. The researcher reached several results, including the high level of the research variables at an average level among the sample members, the presence of a statistically significant difference between the members of the research sample according to the specialization variable (artistic - design) in the future thinking variable in favor of the artistic specialization, and the absence of statistically significant differences in the variable level of ambition. At the end of his research, the researcher reached a number of conclusions and recommendations.